Scheduling flows over LEO constellations on LMS channels. (20th February 2020) - Tauran, Bastien; Lochin, Emmanuel; Lacan, Jérôme; Arnal, Fabrice; Gineste, Mathieu; Kuhn, Nicolas
Summary: Satellite systems typically use physical and link layer reliability schemes to compensate the significant channel impairments, especially for the link between a satellite and a mobile end‐user. These schemes have been introduced at the price of an increase in the end‐to‐end delay, high jitter, or out‐of‐order packets. This is shown to have a negative impact both on multimedia and best‐effort traffic, decreasing the Quality of Experience (QoE) of users. In this paper, we propose to solve this issue by scheduling data transmission as a function of the channel condition. We first investigate existing scheduling mechanisms and analyze their performance for two kinds of traffic: VoIP and best‐effort. In the case of VoIP traffic, the objective is to lower both latency and jitter, which are the most important metrics to achieve a consistent VoIP service. We select the best candidate among several schedulers and propose a novel algorithm specifically designed to carry VoIP over LEO constellations. We then investigate the performance of the scheduling policies on internet‐browsing traffic carried by TCP, where the goal is now the maximize the users' goodput and select the best candidate in this case. Abstract : Satellite systems use physical and link layer reliability schemes to compensate the channel impairments, especially for the link between a satellite and a mobile end‐user. These schemes have been introduced at the price of an increase in the end‐to‐end delay, high jitter, or out‐of‐order packets to the price of a negative impact both on multimedia and best‐effort traffic. This study proposes to solve the problem with a novel scheduling policy which transmits data as a function of the channel condition.